Thermodynamic of Complexation of Lanthanides and Some Transition Metal Ions by 3,5-Dimitro-2'-Hydroxy Benzanilide - Z. Mahmoud, Faten; F. Eid, Mohamed; M. Abo Zied, Sawsan (Asian Journal of Chemistry, 2010)
The stepwise stability constants of (MHL) and (ML) complexes between transition (Cu2+, Ni2+, Co2+, Zn2+, Mn2+, Cd2+,) and lanthanide ions and 3,5-dinitro-2´-hydroxy benzanil (DHBH) in 75% (v/v) dioxane-water at constant ionic strength (0.01 M KNO3) were determined at different temperatures. The thermodynamic parameters for the proton-ligand and metal-ligand stability constants were obtained by the temperature coefficient method. The plot of thermodynamic parameters vs. ionic potential (Z2/r) of the lanthanide elements is not linear as expected from ionic theory. The obtained data support the interpretation of the expanded solvation sphere through the lanthanide series. Anomalies in chelating tendencies at gadolinium indicate a type of cross-over point at which solvent-metal and ligand-metal interaction may occur. Spectrophotometric studies were carried out for Cu2+-, Ni2+- and Co2+-DHB complexes. The solid complexes were isolated and characterized by elemental analysis, conductance, magnetic properties and infra-red spectra.